Learning Motivation in Realizing Achievements: The Secret of Success from Surat Al-Insyirah - M. Irfan Luthfi Rangkuti; Rosniati Hakim; Gusril Kenedi; Munif Zarirruddin Fikri Nordin (Electronic Journal of Education, Social Economics and Technology, 2026)
This problem is motivated by the existence of one of the surahs that explains about learning motivation in realizing achievement, namely surah al-Insyirah. Given the lack and weakness of providing motivation to students in learning activities and the importance of motivation in arousing students' passion for learning. So, the content of surah al-Inshirah can be a source of motivational guidance in learning students to continue to settle in students to achieve the desired goal, namely the realization of achievement in learning. This study aims to discuss how the learning motivation contained in surah al-Inshirah in realizing achievement. This type of research is a library research (Library Research) primary and secondary data sources from tafsir books and other educational books. This research method uses tarbawi tafsir method. The results of this study explain that the learning motivation contained in surah al-Insyirah that can realize achievement is First, spiritual motivation in learning, Second, motivation to foster an optimistic attitude in learning Third, motivation to work hard in learning, Fourth, motivation to have faith in learning.